Environmental issues in the curriculum of the upper primary classes - Srbinovski, Mile (Macedonian Journal of Ecology and Environment, 2003)
With this research, we tried to establish the state with regard to environmental issues in the curriculum of the upper primary classes in our country. Results show to which extent the education for protecting the environmental is realised in accordance with the leading aims and principles of the environmental education. This paper can contribute in the establishment of the needs and possibilities for intensiveness of the formal environmental education.